Wasted Lives: Aging as an Incentive for Reconstruction of Desistance Intentions Among Older Adults in Prison - Avieli, Hila (Criminal justice and behavior, 2020)
There is growing scholarly interest in older adults involved in crime and their lives in prison. However, the specific group of older adults who persistently offend (OAPO) and their desistance intentions has received little attention. The present study aims to explore the lived experiences of OAPO who intend to desist from crime. Seventeen OAPO were interviewed, and an interpretive phenomenological analysis approach was used to analyze the narratives they presented. Participants’ interviews revealed four superordinate themes: (1) insight and change in the lives of OAPO; (2) a series of losses lead to disillusionment with a life of crime; (3) desistance as the only alternative; and (4) fear of death in prison as a catalyst for desistance. The findings suggest that desistance intention among older adults in prison is an individualized process deeply affected by age-related motivations and dynamics.